Land Use Change in the Bukit Rimbang Bukit Baling Wildlife Reserve Area (Case Study in Tanjung Beringin Village) - Muhammad Maulana,; Riky Novarizal, (Sisi Lain Realita, 2024)
Bukit Rimbang Bukit Baling Wildlife Reserve is part of a wildlife reserve forest that has a very high level of ecosystem diversity and very diverse vegetation. With so much diversity or natural resources in the Wildlife Sanctuary, many people abuse this so that there are exploitation activities of forest areas that should not be carried out, the exploitation in question is the activity of land function experts. Researchers use qualitative methods by using descriptive type research. The results showed that Land Use Change in the Bukit Rimbang Bukit Baling Wildlife Reserve Area (Case Study in Tanjung Beringin Village) was motivated by factors of failure to achieve goals and very low economic factors.